Novel Index Value of Fibrinogen and Glucose in Risk Assessment with HOMA-IR - Elango, Kuppusamy Subramaniam; Banu, Narasimhan; Vijayalakshmi, Swaminathan (Asian Journal of Biological and Life Sciences)
In Type 2 diabetes, Insulin resistance leads to microvascular and macrovascular complications. Early diagnosis prevents this complication. Previous studies confirm the association between fibrinogen level and insulin sensitivity but compound effect of glucose and fibrinogen risk levels are not analysed in insulin resistant non-insulin-dependent diabetes. Present study deriving model index with the combination of fibrinogen, glucose value (FiG) and investigating whether linked to HOMA-IR, triglyceride, and glucose (TyG) index also finding alternative index in type 2 diabetes insulin-resistant patients. The study includes 30 Type 2 Diabetic patients and 20 Nondiabetics (control). Fasting serum samples were used to measure Insulin, Triglyceride. A fasting plasma sample was used to measure Glucose and Fibrinogen. The Fasting blood sugar, HOMA-IR, TyG index and the Fibrinogen-Glucose (FiG) novel index between Non-diabetic and Diabetic at a significance of p value < 0.001 level. Serum insulin level shows a significant difference between Non-diabetic and Diabetic at p value < 0.05 level. Also, the receiver operating characteristic curve (ROC) explains the FiG novel index with the good value of are under the curve by 0.877. The FiG index value shows a good correlation with HOMA-IR, and TyG index value also predicts the value of a variable on the value of another variable through linear regression. Hence, it could be suggested for beneficial index value in type 2 diabetes insulin resistant and its complication like cardiovascular diseases.
Keywords: Fibrinogen; Glucose; Index value; Insulin resistant; Triglyceride; Type 2 diabetes